Unveiling the Diagnostic Significance of Calprotectin in Serous Ovarian Carcinoma - Alkis Matsas; Eleni Stamoula; Konstantinos Kontzoglou; Makarios Eleftheriades; Sophia Tsokkou; Panagiotis Christopoulos; Theodoros Panoskaltsis; Eleni Polydorou; Ioannis Sotiropoulos; Theodore Troupis; Dimitrios C. Iliopoulos (Life)
Introduction: Ovarian cancer (OC) is one of the most common gynecologic malignancies and has the highest mortality rate among them. OC has a multifactorial pathogenesis and is characterized by silent onset, progression, and late-stage detection. Therefore, accurate and early detection is of great importance in order to improve survival rates. Emerging evidence reveals that tumor markers are valuable diagnostic and monitoring tools. In this study, we evaluated the aforementioned potential of three markers CA-125, CA 15-3, and serum Calprotectin. CA-125 is a protein that is found elevated in cases of ovarian, breast, and lung cancer. Cancer Antigen 15-3 (CA 15-3) is a protein detected in high levels in women with breast cancer and ovarian cancer and it is significantly elevated in patients with metastasis and recurrence of OC. Calprotectin is a protein released from activated neutrophils, related to inflammatory conditions and can be a potential immune-mediated marker in OC. Purpose: The purpose of this study was to explore the significance of serum calprotectin, CA-125, and CA 15-3 in women diagnosed with serous OC. Methodology: Thirty-eight (38) women with diagnosed OC were included in this research as the study group and twenty-seven (27) healthy women with no history or current diagnosis of OC were included in the control group. Women in both groups shared similar past histories to avoid any other parameters interfering with the study. Our study group was further subdivided into early stage and advanced stage patients. Blood samples were collected from all women of both groups and were examined using ELISA kits to evaluate the levels of the above markers. Results: When comparing patients versus control patients, those with OC exhibited higher levels of Calprotectin compared to healthy individuals. Additionally, Calprotectin showed a statistically significant elevation between the control group and advanced patients. CA-125 remains the current standard of care biomarker exhibiting 90% sensitivity, whereas sensitivities in Calprotectin and CA 15-3 were 60% and 50%, respectively. Conclusions: Serum CA-125 remains the single most valuable biomarker for ovarian cancer, having the highest statistical significance, correlation with disease stage, detecting both early or advanced patients, and sensitivity of 90%. It appears to be a promising inflammatory biomarker in the early diagnosis of ovarian cancer, showing an elevation in patients, while CA 15-3 provides moderate complementary information and exhibits inferior sensitivity when compared to both CA-125 and Calprotectin. The latter appears to be a promising marker and further studies could show if its addition to established protocols could improve early detection, disease progression, or risk stratification. Calprotectin enhances the detection range for ovarian cancer when used alongside CA-125, while this combined approach detected a greater proportion of patients than CA-125 alone, indicating improved diagnostic potential.